Metabolic and Developmental Changes in Germination Process of Mung Bean (Vigna radiata (L.) R. Wilczek) Sprouts under Different Water Spraying Interval and Duration - Insu Lim; Byeong Cheol Kim; Yeri Park; Nam Il Park; Jungmin Ha (Journal of Food Quality)
Mung bean is one of the world’s most important legume crops and is a major protein source, particularly in developing countries. Various polyphenolic compounds and nutrients accumulate in mung bean sprouts during germination. Mung bean sprouts are consumed globally as an excellent food source of bioactive phenolic compounds. The contents of phenols and flavonoids and antioxidant activity were monitored for four days after germination under four different spraying conditions using three mung bean cultivars. On the third day after germination, the sprout extract showed the highest antioxidant capacity. The length and thickness of hypocotyl of mung bean sprouts appeared to be the most suitable for consumption on the third day after germination. Using high-performance liquid chromatography analysis, eight phytochemicals were identified, and neochlorogenic acid was identified for the first time in mung bean sprouts. End products (neochlorogenic acid, chlorogenic acid, vitexin, and isovitexin) showed certain trends in their contents for four days, while intermediates (caffeic acid, catechin, syringic acid, and p-coumaric acid) were highly responsive to watering condition and cultivars. Watering interval significantly affected the length of root and lateral root development. Both cultivars and watering conditions and/or their interaction significantly affected the biochemical and physical traits of mung bean sprouts. The results suggest that watering conditions need to be considered as an important factor to improve food quality of mung bean sprouts. Our phenotypic and metabolic profiling would provide potential information for production of mung bean sprouts that fit consumers’ preferences.